CYBERBULLYING YOUTH ON SOCIAL MEDIA - M. Jorgie Arroyandy; Sandro Saragi; Muhammad Akbar; M Iqbal Andriano Bengkulah; Jimi Mardiansyah; Muhammad Naufal Luthfi; Mahesa Belanti; Siti Fatimah; Bayu Sefryian Saputra (Journal of Islamic Psychology and Behavioral Sciences, 2023)
The purpose of this study is to analyze how often perpetrators carry out cyberbullying actions. The type of research used is a type of survey. Respondents resulting from the survey amounted to N = 58 who were determined using data collection carried out by distributing online questionnaires through the Google form. Meanwhile, this study used the Mixed Method method with a sequential explanatory design. The results of this study can be concluded that most cyberbullying perpetrators have carried out cyberbullying and the majority are involved in low-level cyberbullying with an age range of 17-18 years.